Methoxycarbonylation of 1, 6-hexanediamine with dimethyl carbonate to dimethylhexane-1, 6-dicarbamate over Zn/SiO2 catalyst. Issue 56 (25th May 2016) - Zhang, Lina; Li, Hongguang; Li, Feng; Pu, Yanfeng; Zhao, Ning; Xiao, Fukui
Abstract : The activated Zn(OAc)2 in Zn/SiO2 catalysts facilitates the activation of DMC which leads to better catalytic performance. Abstract : The heterogeneous Zn/SiO2 catalysts for the synthesis of dimethylhexane-1, 6-dicarbamate (HDC) from 1, 6-hexanediamine (HDA) and dimethyl carbonate (DMC) were prepared by incipient impregnation. The catalysts were characterized by BET, TG, FT-IR, TEM and XPS, and the results revealed that the activated Zn(OAc)2 in catalysts was responsible for the main active sites for the reaction. The Zn/SiO2 (300) catalyst exhibited the best catalytic performance with HDA conversion of 96.0% and HDC yield of 68.5% owing to the most amount of activated Zn(OAc)2 and the highest binding energy of Zn 2p3/2 . No obvious deactivation on the catalyst was found after 5 recycles due to the appropriate interaction between Zn(OAc)2 and SiO2 . In addition, the results of in situ FT-IR experiments revealed that DMC was activated by the catalyst to form a stable intermediate that was then attacked by HDA with a typical nucleophilic addition–elimination reaction to produce HDC.